Combination therapy with long-acting bronchodilators and the risk of major adverse cardiovascular events in patients with COPD: a systematic review and meta-analysis. Issue 2 (9th February 2023) - Yang, Mingjin; Li, Yishi; Jiang, Youfan; Guo, Shuliang; He, Jian-Qing; Sin, Don D.
Introduction: Accumulated high-quality data from randomised controlled trials (RCTs) indicate that long-acting muscarinic antagonist (LAMA)/long-acting β2 agonist (LABA) combination therapy significantly improves clinical symptoms and health status in patients with chronic obstructive pulmonary disease (COPD) and reduces exacerbation risk. However, there is a growing concern that LAMA/LABA therapy may increase the risk of cardiovascular disease in patients with COPD. The aim of this paper is to determine whether the use of LAMA/LABA combination therapy modifies the risk of cardiovascular disease in patients with COPD. Methods: Two reviewers independently searched Embase, PubMed and Cochrane Library to identify relevant RCTs of LAMA/LABA or LABA/LAMA/inhaled corticosteroids (ICS) for the management of patients with COPD that reported on cardiovascular end-points. The primary outcome was major adverse cardiovascular events (MACE), which was a composite of cardiovascular death, myocardial infarction or stroke. Results: A total of 51 RCTs enrolling 91 021 subjects were analysed. Both dual LAMA/LABA (1.6% versus 1.3%; relative risk 1.42, 95% CI 1.11–1.81) and triple therapy (1.6% versus 1.4%; relative risk 1.29, 95% CI 1.03–1.61) significantly increased the risk of MACE compared with ICS/LABA. The excess risk was most evident in RCTs in which the average underlying baseline risk for MACE was >1% per year. Compared with LAMA only, LABA only or placebo, dual LAMA/LABA therapy did not significantly increase the risk of MACE, though these comparisons may have lacked sufficient statistical power. Conclusion: Compared with ICS/LABA, dual LAMA/LABA or triple therapy increases cardiovascular risk in patients with COPD. This should be considered in the context of the incremental benefits of these therapies for symptoms and exacerbation rates in patients with COPD, especially in those with a MACE risk of >1% per year. In patients with COPD, the cardiovascular safety of dual LAMA/LABA therapy and triple therapy may be lower than that of ICS/LABA https://bit.ly/3Sk1XWI